2015
DOI: 10.1159/000439404
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Therapeutic Effects of Titanium Dioxide Nanoparticles Are Associated with Oxidative Stress and Cytokine Induction

Abstract: Nanoparticles (NPs) are considered to influence the inflammatory process; however, the precise mechanism and the significance in tumors are still not clear. In this study, when CT26 and LL2 mouse cancer cells were treated with 6-nm anatase titanium dioxide NPs (TDNPs) without ultraviolet irradiation, oxidative stress and induction of inflammatory cytokines were observed. Oxidative stress was further increased by disease-associated conditions such as high glucose concentrations and hypoxia. Inhaled or orally ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…single-strand breaks (SSBs), double-stranded breaks (DSBs)) by direct or indirect effect. With X-ray irradiation, amplified production of ROS and secondary electron from the high-Z nanoparticle result in cytotoxic enhancement on cells (Reproduced with permission from reference: [144], copyright 2018 Elsevier B.V) that titanium dioxide NPs could induce higher levels of inflammatory cytokines production in lung and colon cancer models [75]. Furthermore, small airway epithelial cells exposed to gold NPs could induce protein expression in neighboring lung fibroblasts in co-culture systems.…”
Section: Enhanced Bystander Effectsmentioning
confidence: 99%
“…single-strand breaks (SSBs), double-stranded breaks (DSBs)) by direct or indirect effect. With X-ray irradiation, amplified production of ROS and secondary electron from the high-Z nanoparticle result in cytotoxic enhancement on cells (Reproduced with permission from reference: [144], copyright 2018 Elsevier B.V) that titanium dioxide NPs could induce higher levels of inflammatory cytokines production in lung and colon cancer models [75]. Furthermore, small airway epithelial cells exposed to gold NPs could induce protein expression in neighboring lung fibroblasts in co-culture systems.…”
Section: Enhanced Bystander Effectsmentioning
confidence: 99%
“…NPs could also mediate bystander signalling, for example, small titanium dioxide NPs induce higher levels of oxidative stress and production of inflammatory cytokines. The expression of cytokine macrophage inflammatory protein-1 alpha (MIP-1Ī±) and high-mobility group protein 1 (HMGB1) were found to be expressed in the presence of these NPs, both in vitro and in vivo (Fujiwara et al 2015 ). This may play a role in enhancing oxidative stress as HMGB1 is known to be an inflammatory macrophage-secreted cytokine, which is activated by TNFĪ± (tumour necrosis factor alpha) and IL-1Ī² (interleukin 1 beta) (Andersson et al 2000 ; Tang et al 2009 ).…”
Section: Biological Mechanisms Of Gnp Radiosensitizationmentioning
confidence: 99%
“…Highly reactive hydroxyl acts as a powerful oxidant, resulting in oxidative DNA damage to both single- and double-stranded DNA [ 30 ]. Fujiwara et al found that the oxidative stress produced in response to administration of 6 nm anatase titanium dioxide nanoparticles (on mouse lung and colon cancer cells) was enhanced by high glucose concentrations, acidic pH, hypoxia, high temperature, and the presence of advanced glycation end products [ 32 ].…”
Section: Discussionmentioning
confidence: 99%